Diversity of actinomycetes on plant rhizosphere of karst ecosystem of Gorontalo, Indonesia - YULIANA RETNOWATI; NOVRI YOULA KANDOWANGKO; ABUBAKAR SIDIK KATILI; WAWAN PEMBENGO (Society for Indonesian Biodiversity, 2024)
Abstract. Retnowati Y, Kandowangko NY, Katili AS, Pembengo W. 2024. Diversity of actinomycetes on plant rhizosphere of karst ecosystem of Gorontalo, Indonesia. Biodiversitas 25: 907-915. The objective of this study was to isolate and identify the actinomycetes associated with the rhizosphere of plants in the karst ecosystem. This study was descriptive-quantitative. Soil sampling was conducted at three locations of the karst ecosystem of Gorontalo, i.e., Bangga Hills at Bangga Bubaa Coastal area of Gorontalo District, Hills around Lake Limboto of Gorontalo District, and Oluhuta Beach Hills at Bone Bolango District. Rhizosphere-soil sample was collected from 15-30 cm of soil depth. Isolation of actinomycetes was performed using the plate method. The screening of phosphate-solubilizing bacteria was based on the ability to solubilize phosphates indicated by the clear zone on the Pikovskaya medium. Identification of actinomycetes bacteria based on morphology and molecular characters. The morphology character included the color of aerial and substrate mycelium. Molecular characteristics based on the sequence of 16S rRNA gene compared to sequence data on the gene bank of NCBI. The phylogenetic tree reconstruction was based on the Neighbor-joining algorithm. The results successfully found six isolates, including three actinomycetes isolates, two non-actinomycetes bacteria, and one yeast. They were isolated from the rhizosphere of Malastoma malabathrum, Chromolaena odorata, Cycas rumphii, Leucaena leucocephala, and Jatropha curcas. The actinomycetes isolate showed plant-growth-promoting potential indicated by solubilizing phosphate and Indole 3-Acetic Acid production activities. Based on the molecular analysis, actinomycetes were closely related to Streptomyces aegyptia (MT505707.1:42-1426), Streptomyces sp. GGCR-6 (MH718844.1:5-1391), and Streptomyces carpaticus strain PES-A23 (MH712039).